Mechanical architecture and folding of E. coli type 1 pilus domains - Alvaro Alonso-Caballero (Nature Portfolio, 2018)
The pilus type 1 of uropathogenic E. coli must resist mechanical forces to remain attached to the epithelium. Here the authors use single-molecule force spectroscopy to demonstrate a hierarchy of mechanical stability among the pilus domains and show that the oxidoreductase DsbA also acts as a folding chaperone on the domains.